The Correlation Between Teachers’ Teaching Style and Motivation of Natural Science Students in Learning English at Ten Grade - Permatasari, Chindy Yulia; sujarwati, iis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
This research aims to determine the relationship between the teaching style of English teachers and the motivation of students majoring in science to learn English and to find out what teaching style is preferred by students in learning English. This research used the correlation method with a quantitative design, and the population is class X SMAN 7 Bengkulu City. The technique used was random sampling, where the researcher chose 33 students as a sample. Data collection was carried out through a questionnaire with total of 20 questions regarding the teaching style of English teachers and 20 more questions related to student’s learning motivation. The scale used for data was analyzed using a Likert Scale. Based on the results of research from data analysis, researchers found that the teacher's teaching style that students were most interested in was the expert style, which received a high score of 17%, choosing to strongly agree. Moreover, the findings show Pearson correlation results that there is a significant correlation between the teacher's teaching style and students' motivation in learning English, as explained the significant value is 0.572. The researcher concluded that there was a significant relationship between the teacher's teaching style and the motivation of students majoring in natural science to learn English in class X SMAN 7 Bengkulu City.